2019
DOI: 10.1016/j.jorganchem.2019.120966
|View full text |Cite
|
Sign up to set email alerts
|

Mono- and binuclear Ru(II) arene complexes with (fluoro substituted) picolinic acid: Synthesis, characterization and cytotoxicity

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The obtained results demonstrated that the final complexes exhibit a higher inhibitory effect than both metal salts and ligands. In another study, it was reported that Ru (II) complexes of pyridine‐2‐carboxylic acid displayed moderate antiproliferative effects toward colorectal carcinoma (HCT116) and cervix adenocarcinoma (HeLa) 26 . Buczkowska et al 27 performed a comprehensive study about cytotoxic and antimicrobial activities of Cu (II), Co (II), Pt (II), and Zn (II) complexes with N,O‐chelating heterocyclic carboxylates and reported that these complexes have interesting cytotoxic activities in various human cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results demonstrated that the final complexes exhibit a higher inhibitory effect than both metal salts and ligands. In another study, it was reported that Ru (II) complexes of pyridine‐2‐carboxylic acid displayed moderate antiproliferative effects toward colorectal carcinoma (HCT116) and cervix adenocarcinoma (HeLa) 26 . Buczkowska et al 27 performed a comprehensive study about cytotoxic and antimicrobial activities of Cu (II), Co (II), Pt (II), and Zn (II) complexes with N,O‐chelating heterocyclic carboxylates and reported that these complexes have interesting cytotoxic activities in various human cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Some compounds were shown to exert their anticancer activity by different modes of action compared to established drugs, including enzyme inhibition or crosslinking of DNA or proteins [ 78 , 80 , 81 ]. Numerous polynuclear half-sandwich metal-arene (ruthenium, osmium, rhodium, iridium) complexes have been investigated for their anticancer, antibacterial or antiparasitic properties [ 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ].…”
Section: Introductionmentioning
confidence: 99%
“…(I) These complexes exhibited remarkable cytotoxic action against the A549 and MDA-MB-231 cancer cell lines, which are better than most of the complexes reported in the literature. This behavior probably resulted from the good lipophilicity of this class of complexes.…”
Section: Resultsmentioning
confidence: 89%
“…The slides were stained immediately before analysis using 40 μg mL –1 acridine orange, and the binucleated cells with 1–4 MN were scored at 1000× magnification. Additionally, the frequencies of NPBs and NBUDs were evaluated using the criteria of Fenech et al The NDI was also calculated to evaluate the altered mitotic activity and/or cytostatic effects according to eq : where M1, M2, M3, and M4 are the number of cells with one, two, three, and four nuclei and N is the number of cells assayed. A total of 500 cells per treatment were analyzed or NDI calculated and 1000 binucleated cells for the MN, NPB, and NBUD frequencies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation